PENGARUH PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN STUDI KASUS PADA AMIK XYZ PALEMBANG - Mulyati Mulyati (UNIVERSITAS INDO GLOBAL MANDIRI)
A way a company or personnel department improves job performance, motivation and employee satisfaction is through compensation. Compensation is everything that employees receive as a reward. Compensation is important to employees as individuals because the magnitude of compensation reflects the size of the value of their work among the employees themselves, their families and society. Relative compensation rates indicate their status, dignity and